What climate services do farmers and pastoralists need in Tanzania? - Coulibaly, Jeanne Y.; Mango, Joash; Swamila, M.; Tall, Arame; Kaur, Harneet; Hansen, James (2015)
This report presents final findings from the baseline data collection exercise conducted for Global Framework for Climate Services (GFCS) Adaptation Programme in Africa. The GFCS programme, having a focus on agriculture, food security, heath and disaster risk reduction, is implemented in Tanzania and Malawi. Under the auspices of this GFCS project, the CGIAR research program on Climate Change, Agriculture and Food Security (CCAFS) is responsible to support baseline data collection and monitoring and evaluation (M&E) to evaluate climate services for farmers and pastoralists in Tanzania. The purpose of this report is to inform national partners on farmers’ current access and needs for climate information services. Communities of agro-pastoralists and pastoralists interviewed have little access to climate information, which is generally not associated with agricultural advice. To increase the relevance and communication of climate information in their communities, respondents have recommended training of local extension agents and traditional leaders on the concepts of climate information, having site specific information and using local languages and brochures. The forecasts of greatest interest include start of the rain and expected amount of rainfall over the season. Preferred formats cited by men are radio messages, visits from extension agents while women selected voice message on cell phones and villages communicators. Messengers suggested for radio presenters, local extension agents and village leaders highly recommended by women.